2019
DOI: 10.5045/br.2019.54.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of cell-free DNA as a prognostic biomarker in patients with diffuse large B-cell lymphoma

Abstract: Background Cell-free DNA (cfDNA) has the potential to serve as a non-invasive prognostic biomarker in some types of neoplasia. The investigation of plasma concentration of cfDNA may reveal its use as a valuable biomarker for risk stratification of diffuse large B-cell lymphoma (DLBCL). The present prognostic value of plasma cfDNA has not been widely confirmed in DLBCL subjects. Here, we evaluated cfDNA plasma concentration and assessed its potential prognostic value as an early DLBCL diagnostic to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
2
26
0
1
Order By: Relevance
“…Rivas et al (59), Sun et al (37), and Bohers et al (61) have shown that the detection of cfDNA/ctDNA in DLBCL is related to LDH levels. In contrast, Hur et al (33) and Eskandari et al (34) found no strong correlations between serum LDH and cfDNA in DLBCL. The relationship between cfDNA and Ki-67 is also unclear.…”
Section: Lbs As Biomarkers For Prognosismentioning
confidence: 89%
See 2 more Smart Citations
“…Rivas et al (59), Sun et al (37), and Bohers et al (61) have shown that the detection of cfDNA/ctDNA in DLBCL is related to LDH levels. In contrast, Hur et al (33) and Eskandari et al (34) found no strong correlations between serum LDH and cfDNA in DLBCL. The relationship between cfDNA and Ki-67 is also unclear.…”
Section: Lbs As Biomarkers For Prognosismentioning
confidence: 89%
“…Currently, the most commonly used methods to detect cfDNA include various types of PCR. Commonly used methods to quantify cfDNA/ ctDNA are Qubit for quantification (33,37) and quantitative PCR (34)(35)(36). Although differences in the detection methods used have resulted in heterogeneity among the cfDNA concentrations reported by different studies, all of these studies have reached the conclusion that cfDNA concentrations in NHL cases are higher than those in normal controls.…”
Section: Lbs In Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to protein and molecular biomarkers, cell‐free DNA (cfDNA) has gained significance as a potential biomarker for tumor burden in various cancers including myeloma 4,5 . Although cfDNA is an admixture of normal and tumor‐derived DNA (ctDNA), increased concentration of cfDNA is indicative of higher tumor burden and is a prognostic biomarker of survival in many cancers 4,6 . In MM, ctDNA levels increase with disease progression 7 and genomic variations detected in cfDNA have been used to monitor disease status and response to therapy 8‐10 …”
Section: Introductionmentioning
confidence: 99%
“…indicative of higher tumor burden and is a prognostic biomarker of survival in many cancers. 4,6 In MM, ctDNA levels increase with disease progression 7 and genomic variations detected in cfDNA have been used to monitor disease status and response to therapy. [8][9][10] In this study, we assessed if cfDNA levels are a measure of tumor burden by correlating data from 77 patients with standard clinical biomarkers such as lactate dehydrogenase (LDH), free light chain (FLC) ratio, beta-2-microglobulin (β 2 m), and albumin, in addition to GEP70 risk score.…”
mentioning
confidence: 99%